THE INFLUENCE OF INTERNSHIP AND CAREER GUIDANCE TOWARD THE WORK READINESS OF THE 12TH ACCOUNTING GRADERS OF SMK NEGERI 31 JAKARTA, FOR ACADEMIC YEAR 2017/2018 - Ati Sumiati (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
The aim of this research is to determine the influence of internship and career guidance toward the work readiness of the 12th Accounting graders of SMK Negeri 31 Jakarta for academic year 2017/2018 by using empirical data and facts that are valid and reliable. This research conduct at SMK Negeri 31 Jakarta. The research method used is survey method with quantitative approach. The population in this research is all 12th grade students of SMK Negeri 31 Jakarta as many as 198 people. The sample used as many as 58 people derived from Accounting major . The sampling technique in this study is simple random sampling. All datas are collected using likert scale model questionnaires for internship ( variable X1), career gidance (variable X2) and work readiness (variable Y). Regression equation in this research is Å¶ = 42,081 + 0,256 X1 + 0,228 X2. Based on the result of data analysis, it is known that there is significant partial influence between internship and work readiness. It can be seen from the data analysis that shows the value of tcount of 8,578 is greater than the ttable of 2,004. Also, there is significant partial influence between career guidance and work readiness which has been proved by the value of tcount of 4,730 is greater than the ttable of 2,004. In addition there is a simultaneous influence between intenship and career guidance toward work readiness. It can be seen from the results of data analysis showing the value of Fcount of 53.185 is greater than the Ftable value of 3.165. There is a positive and significant influence between intenship and career guidance toward work readiness with double correlation coefficient 0,744. Thus, the research hypothesis is accepted. The coefficient of determination (R)2 equal to 55,3%. The conclusion of this research is that there is a positive and significant influence between intenship with work readiness. In addition there is also a positive and significant influence between career guidance toward work readiness. Simultaneously, there is a positive and significant influence between internship and career guidance with work readiness. For further research it is advisable to add other independent variables that may affect work readiness variable.